A Fatty Acid Fraction Purified From Sea Buckthorn Seed Oil Has Regenerative Properties on Normal Skin Cells - Dudau, Maria; Codrici, Elena; Tarcomnicu, Isabela; Mihai, Simona; Popescu, Ionela Daniela; Albulescu, Lucian; Constantin, Nicoleta; Cucolea, Iulia; Costache, Teodor; Rambu, Dan; Enciu, Ana-Maria; Hinescu, Mihail E.; et al. (Frontiers in Pharmacology, 2021)
In recent years, natural products research gained momentum, fueled by technological advancement and open availability of research data. To date, sea buckthorn (Hippophae rhamnoides L. [Elaeagnaceae]) plant parts, especially berries, are well characterized and repeatedly tested for antioxidant activity and regenerative properties, in various cell types and tissues. However, fatty acids (FA) have been less investigated in term of biological effects, although they are important bioactive components of the sea buckthorn fruit and oil. The aim of our work was to determine whether sea buckthorn seed oil is a suitable source of FA with regenerative properties on normal skin cells. Using high performance liquid chromatography (HPLC) and liquid chromatography – mass spectrometry (LC-MS) we purified and characterized four fractions enriched in saturated (palmitic) and non-saturated (linoleic, alfa-linolenic, oleic) FA, which were tested for cytotoxicity, cytokine and growth factor production and regenerative effect on normal keratinocytes and skin fibroblasts. Evidence is presented that the palmitic acid enriched fraction was a suitable sea buckthorn seed oil derived product with cell proliferation properties on both skin cell types.